Numerical analysis of laser diode longitudinally pumped solid‐state laser generation dynamics using traveling wave model - Dementjev, Aleksandr; Čiegis, Raimondas; Laukaitytė, Ingrida; Slavinskis, Nerijus (Mathematical Modelling and Analysis, 2010)
A detailed theoretical model for the description of generation dynamics of diode laser longitudinally pumped solid‐state lasers with active and/or passive Q‐switching using traveling wave approach is presented. The results of numerical simulations and analysis show that the distribution of generated laser pulse intensity and the other laser parameters along the resonator is very inhomogeneous. Therefore, the widely used point laser model cannot give accurate results when inside the resonator there are active or passive elements which lead to the strong modulation of the generated pulse intensities. First published online: 09 Jun 2011